1981
DOI: 10.4319/lo.1981.26.2.0378
|View full text |Cite
|
Sign up to set email alerts
|

Primary production under the Ross Ice Shelf, Antarctica1

Abstract: Primary production, defined as fixation of [14C]bicarbonate, occurs in the waters under the Ross Ice Shelf, Antarctica. About 1.5 g C·m−2 is fixed annually. This amount is sufficient to support the observed macrofaunal population and may be due to the activity of chemoautotrophic nitrifying bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 4 publications
7
29
0
Order By: Relevance
“…The only other factor which may play a larger role in regulating the rates of nitrification may be the availability of substrate. Although recent work by Horrigan (1981) has indicated that nitrifiers are active in cold waters (< -2 "C), until this report no organism capable of ammonium oxidation at these temperatures had been isolated. It seems likely that part of the reason Carlucci and Strickland (1968) did not demonstrate low temperature growth with any isolates may have been due to elevated temperatures during initial handling of the samples and the lack of temperature adaptation of their cultures to lower temperatures.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The only other factor which may play a larger role in regulating the rates of nitrification may be the availability of substrate. Although recent work by Horrigan (1981) has indicated that nitrifiers are active in cold waters (< -2 "C), until this report no organism capable of ammonium oxidation at these temperatures had been isolated. It seems likely that part of the reason Carlucci and Strickland (1968) did not demonstrate low temperature growth with any isolates may have been due to elevated temperatures during initial handling of the samples and the lack of temperature adaptation of their cultures to lower temperatures.…”
Section: Discussionmentioning
confidence: 72%
“…In addition to this, the optimum growth temperatures for nitrifiers usually fall within the range of 25 to 35°C. Despite these findings, Horrigan (1981) has recently presented indirect evidence that nitrification is occurring under the Ross Ice Shelf. Antartica, at temperatures below -2"C, and Heneriksen et al (1981) have directly measured nitrification in Danish sediments at 5°C.…”
Section: Introductionmentioning
confidence: 99%
“…probably not a major source of oxidized nitrogen nor a significant mechanism of carbon fixation in the Southem Ocean, except perhaps in areas that lack photosynthetic activity, such as under the Ross Ice Shelf [Horrigan, 1981]. Within-ice nitrification, however, may be of much greater consequence, and will be discussed in a subsequent section of this review.…”
Section: It Appears That While Nitrification Is Occurring In Antarctimentioning
confidence: 96%
“…Under sea ice in Antarctica (Horrigan, 1981), an anchialine cave in the Yucatan Peninsula, Mexico (Pohlman et al, 1997) and the Mississippi River Plume in Gulf of Mexico (Pakulski et al, 2000b) are examples. In these cases, the significance of autotrophic nitrification as an in situ source of organic carbon is enhanced relative to the production of organic matter by photosynthesis.…”
Section: Nitrifying Microorganismsmentioning
confidence: 98%